Resilient architecture for network and control co‐design under wireless channel uncertainty in cyber‐physical systems. Issue 4 (14th August 2018) - Kim, Dohwan; Won, Yuchang; Eun, Yongsoon; Park, Kyung‐Joon
Abstract: In this paper, we propose a resilient architecture for network and control co‐design, Wireless‐Simplex (W‐Simplex), which can ensure control performance by adaptively tuning the network and control parameters against wireless channel uncertainty in cyber‐physical systems. To the best of our knowledge, there has been no research into resilient network and control co‐design in response to the unreliable wireless channel. Our key observation is that rate adaptation may cause significant degradation in control performance or even system instability. This performance degradation is contrary to the intuition that rate adaptation provides a reliable link under wireless channel uncertainty. We explain the cause of this phenomenon and resolve the situation by proposing a resilient co‐design algorithm in an optimization framework. Our simulation study with ns‐2 shows the effectiveness of the proposed scheme to provide resilience of cyber‐physical systems against wireless channel uncertainty. Abstract : In this paper, we propose a resilient architecture for network and control co‐design, Wireless‐Simplex (W‐Simplex), which can ensure control performance by adaptively tuning the network and control parameters against wireless channel uncertainty in cyber‐physical systems (CPS). Our key observation is that rate adaptation may cause significant degradation in control performance or even system instability. We explain the cause of this phenomenon and resolve the situation by proposing a resilient co‐design algorithm in an optimization framework.